Phytochemical screening and evaluation of Monechma ciliatum (black mahlab) seed extracts as antimicrobial agents - Murtada Ahmed Oshi; Abdelkarim Mohmmed Abdelkarim (Mashhad University of Medical Sciences, 2013)
Objective: Tribes in Nubia Mountains regions of Sudan used Monechma ciliatum seeds for common cold and other chest allergic conditions as a traditional medicine. The aim of this paper is to validate this traditional practice scientifically. Materials and Methods: Monechma ciliatum seeds were screened for major phytochemical groups using standard methods. Different extracts were bioassayed in- vitro for their bioactivity to inhibit the growth of pathogenic bacteria and fungi. Results: Phytochemical screening results showed the presence of flavonoids, tannins, triterpens, and anthraquinones. Staphylococcus aureus was found to be sensitive to both water extract with zones of inhibition 22 - 26 mm at concentrations of 50 and 100mg/ml and ethanol extract 17 mm at concentration of 100 mg/ml. The growth of Klebsiella pneumoniae was inhibited by ethanol extract with zones of inhibition equal to 16, 26, and 33 mm at concentrations of 50, 100, and 150 mg/ml, respectively. Pseudomonas aeruginosa was insensitive to all extracts used. Similarly, all used fungi were found to be insensitive to extracts used. The minimum inhibitory concentrations of the extracts against microorganisms were ranged from 12.5 to 25 mg/ml. Conclusion: The findings of the current study support the traditional uses of the plant's seed in the therapy of respiratory tract infections caused by Staphylococcus aureus and Klebsiella pneumoniae.